A intersecção religiosa entre o povo Kaingang e o pentecostalismo na terra indígena Guarita: apropriações e ressignificações - Ferrari, Odêmio Antonio (2012)
The objectives of this study start with the verification that in the Guarita Indiginous Land (TIG) there was established a solid insertion of pentecostalism with the predominance of the Assembly of God Evangelical Church for more than five decades. Being two different and similar collective wholes in the socio-cultural charactaristics, the question arises about which symbolic elements, message, and the format of religious performance that made the evangelical Pentecostalism be chosen by the Kaingang society. Forming a full network of Pentecostal churches, joining the villages, having permanent religious services lead by a pentecostalist indigenous hierarchy, showing a strong participation of Kaingang in the dynamic of evangelism based on the Pentecostal tripod: pietistic doctrine, puritan-sectarian morality and emotional ritual.Thus, the Lutheran and Catholic Churches encounter little receptivity in TIG. The factors and strategies of the interconnection between the Kaingang and the Pentecostalism with the assembly predominance in TIG, aiming to sniff out the consequences to the indigenous society. Also, researching the anthropological elements that form the relegation of beliefs and myths, the religious and ecclesial values of Pentecostal evangelization, the social-cultural profiles of the traditions in the two collective wholes, in mutual relation. In this process of religious-cultural intersection it is not possible to come to a conclusion about an effective conversion of the beliefs and Kaingang traditions. But, there occurs a relationship of mutual acceptance and grouping in the believer, through a re-alligning of the religious-cultural values, producing a energy of meaning to the Kaingang society broken by a history of crises with a distinct people, in contact with a developing society Therefore, an anthropological approach in the research is based on the studies about the Kaingang in other indigenous lands and continuous looking at the presence of evangelical pentecostolism in the reality of TIG. I have established as a supposition of the research: the evangelical proselitism with the predominance of the Assembly of God Evangelical Church, followed by the God is Love Pentecostal Church, was able to have a strong receptivity in the Indigenous Land of Guarati, due to its strategy that established bridges of interconnection, in making a connection with the imaginary and the indigenous religious-cultural values, interacting in the Kaingang social organization. A mutual and differentiated receptivity between Pentecostalism andthe Kaingang resulting in a process of appropriationand re-signification of a religious Kaingang,provocative of change in the beliefs, values andindigenous conducts, aggravating the tradition and the hierarchical culture in the village and, in relation to anevolving society, in the religious and civil ambit